Characterisation of Epitopes on Human Tissue Plasminogen Activator Recognised by a Group of Monoclonal Antibodies - MacGregor, Ian R; Micklem, Lisel R; James, Keith; Pepper, Duncan S (Thrombosis and Haemostasis, 1985)
Seven mouse monoclonal antibodies have been produced against human melanoma tissue plasminogen activator (t-PA). They were specifically bound to 125I t-PA but not 125I urokinase (u-PA) and inhibited t-PA, but not u-PA, activity in plasminogen- rich 125I fibrin wells. Three of the antibodies directly inhibited the amidolytic activity of t-PA and the two most effective also bound near the active site histidine residue as determined by competition experiments using active site blocking agents. Several antibodies interfered with the fibrin binding properties of t-PA. One antibody neither interacted with the active site nor inhibited fibrin binding but still effectively quenched t-PA activity in fibrin wells suggesting that it masks another region of the molecule necessary for effective biological activity.
Keywords: Epitopes; Tissue plasminogen activator; Monoclonal antibodies; Active site